Desenvolvimento de formulações de interesse farmacêutico e cosmético a partir de óleos vegetais derivados de plantas cultivadas no RS - Rigo, Lucas Almeida (2011)
This work aimed to use the rice bran, soybean or sunflower seed oil as alternative raw materials for the development of pharmaceutical and cosmetic dosage forms. In the first chapter sunscreen cosmetic formulations were prepared from gel-cream containing rice bran or soybean oil at different concentrations, using an organic sunscreen (benzophenone-3). The influence of these oils on the following characteristics was assessed: pH, spreadability, rheological behavior, and in vitro sun protection factor. The formulations showed suitable physical and chemical characteristics, non-Newtonian rheological behavior, and spreadability dependent on the concentration of the oil. The sun protection factor was around 10 regardless of the type and concentration of oil used. In the second chapter, lipid-core nanocapsules were prepared by interfacial deposition of preformed polymer containing rice bran, soybean or sunflower seed oil. The physicochemical parameters analyzed were pH, particle size, polydispersity index, zeta potential, morphological characteristics, and stability. The type of vegetable oil did not have influence on the physicochemical characteristics of the formulations, which remained adequate and stable during the 3 months of storage. Moreover, based on the genotoxicity and proliferative activity studies we can suggest that none of the formulations present risks to the environment. In the third chapter, nanocapsule formulations containing the three vegetable oils and a model drug (0.5 mg/mL) were prepared to evaluate the effect of the oils on the in vitro drug release. The drug was successfully encapsulated in all nanocapsule formulations with total drug close to the theoretical value. The in vitro drug release study from nanocapsules showed that the controlled release follows a biexponential regardless of the type of vegetable oil. The nanocapsule formulations containing the sunflower seed oil provided higher drug release control, followed by the nanocapsule formulations containing soybean and rice bran oil, showing that the type of the vegetable oil influences the drug release profile. Through these works the technological feasibility to use the rice bran, soybean or sunflower seed oil was demonstrated as an alternative source of viable raw material for obtaining pharmaceutical formulations of pharmaceutical and cosmetic interest.